2023
DOI: 10.3390/nu15071724
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Calcium Supplementation and Urolithiasis: A Controversial and Multifaceted Relationship

Abstract: Patients with urolithiasis, and particularly those with hypercalciuria, frequently have a marked reduction of bone mineral content up to the levels of osteoporosis, with a significant increase in bone fracture risk. For these reasons, the indication to prescribe vitamin D and/or calcium supplementations is very frequent in such patients. On the other hand, both calcium supplementation, and even more vitamin D therapy, can worsen the risk of developing urolithiasis by increasing calcium, phosphate, and oxalate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…The most common stone phenotype is calcium-based, and the pathogenesis of kidney stones may be associated with metabolic pathways of calcium and vitamin D ( 13 ). However, studies on the relationship between the two and kidney stones are controversial ( 27 ). Previously, numerous prospective studies have indicated a strong correlation between increased dietary calcium intake and a decreased risk of kidney stones, a trend that is in line with our own findings ( 14–18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common stone phenotype is calcium-based, and the pathogenesis of kidney stones may be associated with metabolic pathways of calcium and vitamin D ( 13 ). However, studies on the relationship between the two and kidney stones are controversial ( 27 ). Previously, numerous prospective studies have indicated a strong correlation between increased dietary calcium intake and a decreased risk of kidney stones, a trend that is in line with our own findings ( 14–18 ).…”
Section: Discussionmentioning
confidence: 99%